Sound detection of gamelan musical instruments using teachable machine - Yunitasari, Yessi; Asyhari, Moch Yusuf; Kurniawati, Inung Diah; STT, Latjuba Sofyana (SHM Publisher, 2025)
Gamelan is an instrument of musical expression that has an aesthetic function related to social, moral, and spiritual values. Gamelan consists of a variety of musical instruments that have a unique sound. In this study, the sound detection of nine gamelan musical instruments was carried out using a teachable machine. The gamelan musical instruments detected included gong, kenong, saron, bonang, gambang, kendang, flute, siter, and rebab. The algorithm used is CNN. The CNN algorithm has a fairly good performance for the sound detection process. The test results of the built model show an